Promotional Strategies for MSMEs through Social Media to Boost Sales During the New Year: Implications for Community Welfare - Azzaakiyyah, Hizbul Khootimah; Novianti, Rini; Santosa, Sonny (PT. LITERASI SAINS NUSANTARA, 2024)
This study aims to analyze the promotional strategies employed by micro, small, and medium enterprises (MSMEs) via social media to boost sales during the New Year period and their implications for community welfare. Using a qualitative literature review approach, data were gathered from 20 selected scientific articles published between 2014 and 2024 on Google Scholar. Descriptive analysis was used to identify trends, strategies, and the impact of digital promotion on MSMEs. The findings reveal that social media platforms such as Instagram, TikTok, Facebook, and WhatsApp are effective tools for reaching a broad consumer base at a low cost. Creative promotional strategies aligned with New Year themes were shown to increase MSME sales by 50%–70% in several cases, while also generating additional employment opportunities. Besides economic benefits, social media promotions also positively impact the well-being of local communities. This study provides practical insights for MSMEs to design effective digital marketing strategies and supports governmental efforts to enhance the digital literacy of MSMEs to ensure business sustainability.